Q. 7 A24.0( 8 Votes )

# If <span lang="EN

If y = 2-√3

Then; Simplifying it we get;  = = 2 + √3

y + = 2 – √3 + [2 + √3] = 4

(y + )2 = y2 + [ ]2 + 2 × y × (4)2 = y2 + [ ]2 + 2

y2 + [ ]2 = 16 – 2 = 14

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics